Enhanced recognition memory in grapheme-color synaesthesia for different categories of visual stimuli - Ward, Jamie; Hovard, Peter; Jones, Alicia; Rothen, Nicolas (Frontiers in Psychology, 2013)
Memory has been shown to be enhanced in grapheme-colour synaesthesia, and this enhancement extends to certain visual stimuli (that don’t induce synaesthesia) as well as stimuli comprised of graphemes (which do). Previous studies have used a variety of testing procedures to assess memory in synaesthesia (e.g. free recall, recognition, associative learning) making it hard to know the extent to which memory benefits are attributable to the stimulus properties themselves, the testing method, participant strategies, or some combination of these factors. In the first experiment, we use the same testing procedure (recognition memory) for a variety of stimuli (written words, nonwords, scenes, and fractals) and also check which memorisation strategies were used. We demonstrate that grapheme-colour synaesthetes show enhanced memory across all these stimuli, but this is not found for a non-visual type of synaesthesia (lexical-gustatory). In the second experiment, the memory advantage for scenes is explored further by manipulating the properties of the old and new images (changing colour, orientation, or object presence). Again, grapheme-colour synaesthetes show a memory advantage for scenes across all manipulations. Although recognition memory is generally enhanced in this study, the largest effects were found for abstract visual images (fractals) and scenes for which colour can be used to discriminate old/new status.